2007
DOI: 10.1590/s1516-35982007000700021
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do tamanho de partícula e da altura de colheita de plantas de milho (Zea mays L.) para ensilagem na produção do novilho superprecoce

Abstract: RESUMO -O experimento foi conduzido com o objetivo de avaliar o efeito do tamanho de partícula (pequena: 0,2 a 0,6 cm ou grande: 1,0 a 2,0 cm) e da altura de corte de plantas de milho para ensilagem (baixa: 15 cm ou alta: 39 cm) sobre o consumo de MS e o desempenho de novilhos em confinamento. Foram avaliados os seguintes tratamentos: silagem de partícula pequena com altura de corte baixo; silagem de partícula grande com altura de corte baixo; silagem de partícula pequena com altura de corte alto; e silagem de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Restle et al (2002) failed to report any difference for ADG in 12-month-old feedlot Braford steers fed on corn silage with two cutting heights (16 and 46 cm). Posteriorly, Neumann et al (2007) did not report any difference for ADG (1.5 kg) in feedlot Charolais bulls fed on corn silage with two cutting heights (15 and 39 cm).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Restle et al (2002) failed to report any difference for ADG in 12-month-old feedlot Braford steers fed on corn silage with two cutting heights (16 and 46 cm). Posteriorly, Neumann et al (2007) did not report any difference for ADG (1.5 kg) in feedlot Charolais bulls fed on corn silage with two cutting heights (15 and 39 cm).…”
Section: Resultsmentioning
confidence: 76%
“…Since the mean feed efficiency was 5.9, these results were similar to those (5.7) obtained by Restle et al (2002) in young steers fed on hybrid corn silage in two cutting heights (20 and 42 cm). However, Neumann et al (2007) reported similar feed efficiency for crossbred bulls fed on corn silage harvested at a height of 15 cm (6.2) and 38 cm (5.7). Efficiency of dry matter (5.9) may be due to the genetic degree of the animals (F1 -½ Nellore vs. ½ Angus), formulated diet (high protein rate -12% and energy -74% TDN), feedlot time (64 days) and animal gender (bulls).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Neumann et al [24] found that undesirable fermentation modified the composition of silage, resulting in low intake because products such as NH 3 -N and VFA were formed with acetic acid especially negatively affecting the acceptability of silage by animals due to reduced palatability. The acetic acid-producing bacteria act first due to the presence of oxygen but are soon inhibited by the increase in the temperature and acidity of the medium.…”
Section: Resultsmentioning
confidence: 99%
“…Wu & Roth (2005) gathered data from 11 studies utilizing corn silage harvested at two cutting heights, and observed that the high cutting height (50 cm) increased the crude protein and net energy levels, and the neutral detergent fiber digestibility, promoting an increase in milk production of dairy cows, per ton of silage produced, when compared to the usual cutting height (17 cm). Neumann et al (2007b), evaluating the performance of confined Charolais steers, fed corn silages produced with different particle sizes and cutting heights, observed that when the plants were cut at 38.6 cm of height, the nutritive value of the silage improved and, consequently, the dry matter digestibility and animal performance also improved, when compared with a cutting height of 15.2 cm.…”
Section: Introductionmentioning
confidence: 99%